SISTEM INFORMASI ENTREPRENEURSHIP DAN USAHA KECIL MENENGAH (UKM) (Jurnal Pilar Nusa Mandiri, 2013)
With the growing world of technology, especially Internet-based technologies such as a website where all the desired information can be easily and cheaply obtained. The presence of this information portal website is expected to help the public to get real-time information about entrepreneurship and SMEs in Indonesia. In building this system the authors use the support tools with the object-oriented methodology for UML. UML supports object-oriented programming languages or OOP (Object Oriented Programming), web applications, PHP and MySQL, whereas for the author photo editor using Adobe Photoshop 7.0 and Macromedia Dreamweaver media to write PHP scripts. Browser serves to preview PHP commands that have been run on a web server. Examples of browsers are Internet Explorer, Netscape Navigator, Opera, Firefox in this case I use Mozilla Firefox. The resulting system of tools above will be much better in terms of efficiency, effectiveness, reliability, and flexibility for UML is an object-oriented programming language. And other tools that are easy to understand because it is easy to learn.